C&D integrativo: contribuições para o cuidado da criança em uma unidade básica de saúde - Lima, Thallita Monalisa Sizenando Souza (2022)
The child psychomotor development can be affected by several factors, being observed in the daily life of the Basic Health Unit of Góes, Rural Area of the municipality of Apodi in Rio Grande do Norte, a considered number of complaints of mothers related to child development. In this sense, the Family Health Team adapted the care process in the Ministry of Health's Growth and Development Program, through the production of two Manuals with guidelines to assist and empower parents and/or caregivers in the demands, thus entitlement of “integrative C&D”. The present study is of the Action-Research type of evaluative nature, with a qualitative analysis approach before and after the implementation of integrative C&D. The two Manuals contain, in an interactive playful way, specific guidelines to help parents and/or caregivers, in activities to stimulate psychomotor development, in children's entertainment, in addition to quick, easy and cheap recipes to help mothers in the use of food fresh, produced by the residents of the region. Also noteworthy is the implementation of integrative multidisciplinary care during consultations. The research subjects are mothers of children aged 12 to 48 months who reported some of these complaints of behavioral changes. Data evaluation will be guided by the steps of Bardin's content analysis. This work was proposed to the Ethics and Research Committee of the Ethics and Research Committee of the Hospital Universitário Onofre Lopes-CEP HUOL, under protocol number 5,078,004, according to resolution 466/1. Through this study, we sought to innovate and evaluate in an integrative way, the process of caring for the child in the Basic Health Unit, aiming at strengthening the team's bond with the family, better monitoring the development of cognition and psychomotricity, in addition to providing two manuals produced by the team for use by mothers and caregivers of these children.